Wood-based carbon storage in the Mackenzie River Delta: the world's largest mapped riverine wood deposit - Sendrowski, A; Wohl, E; Hilton, R; Kramer, N; Ascough, P (Wiley, 2023)
The Mackenzie River Delta (MRD) has been recognized as an important host of river-derived wood deposits, and Mackenzie River wood has been found across the Arctic Ocean. Nevertheless, we lack estimates of the amount of carbon stored as wood and its age in the delta, representing a gap in carbon cycle estimates. Here, we use very high-resolution satellite imagery and deep learning to map wood deposits in the MRD, combining this with field data to measure the stock and age of wood-based carbon. We find >400,000 individual large wood deposits, collectively storing 3.1 × 1012 g-C, equating to 2 × 106 g-C ha−1 across the delta. Sampled wood pieces date from 690 AD to 2015 AD but are mostly young with ∼40% of the wood samples formed after 1955 AD. These estimates represent a minimum bound on an important surficial, potentially reactive, carbon pool compared to other deeper carbon stocks in permafrost zones.